Alzheimer’s disease: impact on elderlys’s and caregiver’s quality of life (Research, Society and Development, 2021)
Objective: Analyze the repercussion of the diagnosis of Alzheimer’s Disease on quality of life of the elderly and their caregivers. Methods: This is an integrative review of the literature based on the guiding question: What are the challenges faced by patients with Alzheimer’s Disease and their caregivers? Scientific articles were selected, published between 2012 and 2018, on the Virtual Health Library (VHL) and Scientific Eletronic Library Online (SCIELO). The descriptors “Alzheimer’s Disease”, “Caregivers”,” Aged” and boolean operator AND were used for the search. Were selected eighteen scientific articles available in full in the mentioned databases, with language in portuguese, english or spanish and publication during the proposed period. Were excluded abstracts, theses and monographs. Results: The analyzed studies demonstrated that the diagnosis of Alzheimer’s Disease (AD) involves stressful situations, as cognitive decline of the elderly changes daily life of the family and requires complete assistance of caregivers, that, frequently, feel overloaded and have higher risk of health problems. Conclusions: The care process in Alzheimer's Disease (AD) has an impact on the quality of life of Alzheimer's patients, their caregivers and relatives. Seeing the trend of population ageing, this is a challenging setting, that requires holistic view of the condition of the elderly and their caregivers.